Distant Metastasis from Benign Solitary Fibrous Tumor of the Kidney - Sasaki, Hideo (S. Karger AG, 2013)
Solitary fibrous tumor (SFT) rarely occurs in the kidneys, and only one reported case of renal SFT has shown distant metastasis. We report the second case of renal SFT exhibiting distant metastasis. A 48-year-old man was referred to our hospital because of a right renal mass. An abdominal CT scan detected a large renal tumor, which was suspected to be a renal cell carcinoma. Right radical nephrectomy was performed, and the tumor was found to measure 28 × 18 × 10 cm. The pathological diagnosis was benign solitary fibrous tumor of the kidney. Eight years after the operation, lung and liver metastases developed. Pulmonary segmentectomy and partial hepatectomy were performed. The pathological diagnoses of these resected tissue specimens were compatible with benign SFT.